Harnessing Artificial Intelligence for Smart City Development: Benefits and Challenges in Lagos State, Nigeria - Ayegbo, Olufemi John; Abas, Aliu; Momodu, Mustapha; Achuenu, Anthony (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
This study investigates the role of Artificial Intelligence (AI) in the development of smart cities in Lagos State, Nigeria, with a particular focus on its potential benefits and implementation challenges. Employing a descriptive survey research design, the study collected quantitative data from 250 purposively selected respondents across five local government areas—Apapa, Ibeju-Lekki, Surulere, Lagos Island, and Lagos Mainland. The participants, comprising residents, urban planners, policymakers, and other stakeholders, completed structured questionnaires designed to evaluate perceptions of AI's contributions to urban mobility, energy efficiency, public safety, waste management, healthcare, and governance.Data were gathered using a validated four-point Likert scale instrument, with a Cronbach’s Alpha reliability coefficient of 0.82. Descriptive statistics revealed strong agreement among respondents regarding the positive impact of AI on efficient urban planning, traffic management, resource optimization, and quality of life. One-sample t-tests further confirmed the statistical significance of these perceptions, with all items yielding p-values below 0.05 when compared to the baseline value of 2.0. However, challenges such as high implementation costs, limited access to reliable infrastructure, and a shortage of technical expertise were also significantly acknowledged.The findings underscore AI’s transformative potential in urban development while highlighting the need for strategic investments in infrastructure and human capital. The study concludes with policy-oriented recommendations to facilitate the successful integration of AI technologies in the pursuit of sustainable and inclusive smart city initiatives.